Strategies for research groups to boost their degree of consolidation - Vázquez Cid de León, Carlos; Montesinos González, Salvador; Aguilar Cruz, Conrado; Carazo Luna, José Alfredo (Revista Venezolana de Gerencia, 2022)
In Mexico, formal research groups are known as Academic Bodies (AB) and are recognized by a government program called Program for Professional Teacher Development (Prodep). Universities do not always manage these formal research groups and their evolution, for this reason the objective of this research is to analyze the universities in the state of Oaxaca that have AB to identify the variables that affect the evolution in its degree of consolidation and propose strategies for its management. The methodology used is the Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis and as a result, an operationalization of variables was obtained according to the operating rules of PRODEP in Mexico for the AB. The measurement of the productivity of the AB, the variables knowledge regarding the rules of operation, invariable features of the consolidated academic bodies, strategic planning and evaluation instrument were studied. In addition, a strategic plan was developed in order to encourage the members to continuous improvement and thus have an increase in the consolidation of the AB.